A Comparative Study of an Immediate Effect of Thai Traditional Herbal Steam and Conventional Steam on Body Flexibility in Women Aged 30-45 Years - Kumfu, Sirintip; Parasin, Nichapa (Srinagarind Medical Journal, 2017)
Background and Objective: Working for long periods or incorrect posture may result in muscle injury. One of factors that cause a muscle injury is lack of body flexibility. There are many ways to increase body flexibility and steam is one of alternative method. The purpose of this study was to compare an immediate effect between Thai herbal steam and conventional steam on body flexibility in female volunteers who have low to moderate level of body flexibility aged 30-45 years. Methods: Twenty nine females aged 30-45 years old were divided into two groups. Fifteen subjects received Thai herbal steam treatment while 14 subjects received conventional steam. Both groups were treated for 30minutes. The volunteers were evaluated flexibility of lower back and posterior thigh muscles by sit and reach test and flexibility of shoulder muscle group by shoulder girdle flexibility test. The flexibility were measured at before and the end of steam. Results: The results showed that after steam the flexibility of left and right shoulder in the conventional steam and Thai herbal steam groups were improved -10.21 ± 9.51, -7.28 ± 7.56 cm and -7.07 ± 8.44, -2.53 ± 6.25 cm, respectively, the flexibility of lower back and posterior thigh muscles were 7.96 ± 5.90, 12.97 ± 6.26 cm, respectively.After steam no significant difference between groups of shoulder flexibility (p = 0.07 and 0.35, respectively). Only, Thai herbal steam group was significantly increased the flexibility of lower back and hamstring muscles more than the conventional steam group (12.97±6.26, 7.96±5.90 cm.p=0.04). Conclusion: Thai herbal steam and conventional steam can increase the flexibility of lower back and hamstring muscles and flexibility of the shoulders. However, Thai herbal steam can improve the body flexibility better than conventional steam. การศึกษาเปรียบเทียบผลทันทีระหว่างการอบไอน้ำสมุนไพรไทยและการอบไอน้ำธรรมดาต่อความยืดหยุ่นของร่างกายในเพศหญิง อายุ 30-45 ปี ศิรินทิพย์ คำฟู *, ณิชาภา พาราศิลป์ สาขาวิชากายภาพบำบัด คณะสหเวชศาสตร์ มหาวิทยาลัยพะเยา หลักการและวัตถุประสงค์: การทำงานเป็นระยะเวลานานในท่าทางที่ไม่ถูกต้อง อาจส่งผลให้เกิดการบาดเจ็บของกล้ามเนื้อ ปัจจัยหนึ่งที่ก่อให้เกิดการบาดเจ็บของกล้ามเนื้อ คือการขาดความยืดหยุ่นของร่างกาย การเพิ่มความยืดหยุ่นมีหลายวิธีหนึ่งในนั้นคือการอบไอน้ำการศึกษานี้จึงมีวัตถุประสงค์เพื่อเปรียบเทียบผลทันทีระหว่างการอบไอน้ำสมุนไพรไทยและการอบไอน้ำต่อความยืดหยุ่นของร่างกายในอาสาสมัครเพศหญิงที่มีความยืดหยุ่นของร่างกายระดับต่ำถึงปานกลาง วิธีการศึกษา: อาสาสมัครเพศหญิง อายุ 30-45 ปี จำนวน 29 ราย แบ่งเป็นสองกลุ่ม ได้แก่กลุ่มที่ได้รับการอบไอน้ำจำนวน 14 ราย และกลุ่มที่ได้รับการอบไอน้ำสมุนไพรไทย 15 คน ทำการอบไอน้ำเป็นระยะเวลา 30 นาที ประเมินความยืดหยุ่นของกล้ามเนื้อหลังส่วนล่างและกล้ามเนื้อต้นขาด้านหลัง โดยการทดสอบการนั่งงอตัว (Sit and reach test) และประเมินความยืดหยุ่นของข้อไหล่ด้วยการทดสอบการเคลื่อนไหวของข้อไหล่ (Shoulder girdle flexibility test) ก่อนและหลังการอบไอน้ำ ผลการศึกษา:ผลการศึกษาพบว่ากลุ่มอบไอน้ำแบบธรรมดาและกลุ่มอบไอน้ำสมุนไพร มีค่าความยืดหยุ่นของข้อไหล่ข้างซ้ายและขวาหลังได้รับการอบไอน้ำ ได้แก่ -10.21 ± 9.51,-7.28 ± 7.56 ซม. และ -7.07 ± 8.44, -2.53 ± 6.25 ซม. ตามลำดับความยืดหยุ่นของกล้ามเนื้อหลังส่วนล่างและกล้ามเนื้อต้นขาด้านหลังได้แก่ 7.96 ± 5.90, 12.97 ± 6.26 ซม.ตามลำดับ และเมื่อเปรียบเทียบความยืดหยุ่นของข้อไหล่ข้างซ้ายและขวา ระหว่างกลุ่มไม่พบความแตกต่างกันอย่างมีนัยสำคัญทางสถิติ (p =0.07 และ 0.35 ตามลำดับ) มีเพียงความยืดหยุ่นของกล้ามเนื้อหลังและขาในกลุ่มที่ได้รับการอบไอน้ำสมุนไพรมีค่ามากกว่ากลุ่มที่ได้รับการอบไอน้ำแบบธรรมดาอย่างมีนัยสำคัญทางสถิติ ได้แก่ (12.97 ± 6.26, 7.96 ± 5.90 ซม. p =0.04) สรุป: การอบไอน้ำสมุนไพรไทยและการอบไอน้ำสามารถเพิ่มความยืดหยุ่นของกล้ามเนื้อหลังส่วนล่างและกล้ามเนื้อต้นขาด้านหลังและความยืดหยุ่นของข้อไหล่ได้ แต่อย่างไรก็ตามการอบไอน้ำสมุนไพรไทยสามารถเพิ่มความยืดหยุ่นของกล้ามเนื้อหลังส่วนล่างและกล้ามเนื้อต้นขาด้านหลังได้ดีกว่าการอบไอน้ำแบบธรรมดา